Pemanfaatan Limbah Bunga Lontar (Borassus flabellifer L) sebagai Adsorben Rhodamin B - Iin, Iin Novianty; Rahmiani Gani (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2025)
A study has been conducted on the utilization of activated carbon from palmyra flower waste (Borassus flabellifer L.) as an adsorbent for rhodamine B dye. The purpose of this study was to determine the optimum conditions for activated carbon from palmyra flower waste activated with phosphoric acid (H3PO4) in the adsorption process of Rhodamine B. The preparation of activated carbon from palmyra flower was carried out using the clin drum method. The adsorption process was carried out with variations in contact time and adsorbate concentration. The optimum conditions for the adsorption process of rhodamine B dye were obtained at a contact time of 90 minutes and an adsorbate concentration of 30 ppm with adsorption efficiency values of 50.22% and 77.13%, respectively.